Towards environmentally responsible finance: How ESG and carbon efficiency shape green bond allocation in Asian firms - Soegiarto, Kelvin; Wedari, Linda Kusumaning (Edelweiss Applied Science and Technology, 2026)
The accelerating environmental challenges in Asia have heightened the urgency for sustainable financing mechanisms that can balance economic growth with environmental preservation. Green bonds have emerged as a key financial instrument to mobilize capital for low-carbon and environmentally responsible projects. This study empirically examines the effect of Environmental, Social, and Governance (ESG) performance on the proportion of green bond issuance among publicly listed firms in Asia from 2019 to 2023. Using 177 firm-year observations, this research also examines the moderating role of firm size in the relationship between ESG performance and green bond issuance. The empirical results show that ESG performance has a significant negative impact on the proportion of green bonds issued. Furthermore, firm size negatively moderates the relationship between ESG performance and green bond issuance. Theoretically, this study contributes to the integration of signaling theory and capital structure in the context of sustainable finance in emerging Asian markets. The findings provide valuable insights for policymakers, regulators, and investors to design more targeted incentives and improve disclosure standards that encourage green financing among firms of different sizes and ESG maturity levels, while supporting a framework that enhances transparency, accountability, and inclusiveness in Asia’s transition to a green economy.